Technical miscegenation of the Spanish and popular guitar in the accompaniment of the song hall from Ecuador - Figueroa Solano, Marco Fernando (Unaciencia, Revista de Estudios e Investigaciones, 2018)
Nowadays, the pasillo continue being the favorite musical genre of most Ecuadorians. It has being adapted to new versions which has made it popular again. The guitar is the essential instrument in the accompaniment of the Ecuadorian Pasillo. Therefore, the intention of the current investigation is to expose technical, popular, and academics characteristics that contribute with a mestizaje miscegenation musical to play the Ecuadorian pasillo in the guitar.
Keywords: Array; Array; Array; Array; Array; Array; Array